The Reality of The Practice of Crisis Management at King Abdulaziz University – A Field Study at King Abdulaziz University – - Alghamdi, Samyah Saad Bakeet Mohamed; Alshamasi, Areej Abdulrahman Nasser (Journal of Risk and Crisis Management, 2021)
The study aimed to identify the reality of the practice of crisis management at King Abdelaziz University, from the point of view of administrative staff at King Abdelaziz University for the year 1440 AH to achieve the goal of the study. The study is important because it frames the current reality of the levels of crisis management practice at King Abdulaziz University in the Kingdom of Saudi Arabia, and thus assumes the availability of skills (planning, coordination, and organization) in the practice of crisis management at King Abdulaziz University by relying on the questionnaire as a tool for data collection, The analytical descriptive approach was used, using the questionnaire as a tool to collect data, and the study tools were applied to a random sample It reached (200) administrative employees, and the study reached a set of results, the most important of which are: It turned out that the degree of crisis management practice at King Abdelaziz University came with a (high) degree from the point of view of the study sample individuals, and came in the first order after planning with an arithmetic average of (3.81) Then, after coordination with an arithmetic average of (3.32), while it came in the last order after organization with an arithmetical average of (3.15), it was also shown that there were no statistically significant differences at the level of significance (0.05) in the opinions of the individual sample of the research on "the degree of crisis management practice At King Abdelaziz University "according to the two variables (gender, nature of work, years of experience), and in light of these results, the study presented a set of recommendations, the most prominent of which are: holding periodic meetings between academic leaders in Saudi universities and managers of crisis departments in universities, for whom Fostering the problems and crises that the university is going through, and setting up a mechanism to overcome them, working to give the crisis departments in the Saudi universities more freedom; To create crisis management, and to provide trained and qualified cadres working to provide them with appropriate support, to work in coordination with universities departments to attend more training courses, workshops, and scientific seminars aimed at raising their awareness of how to manage the crises to which the university is exposed, working to renew Updating the established crisis management plans and conducting more training experiences; To deal with different crises to test the efficiency and effectiveness of these plans.